Ocular morbidity in school children in eastern region of Nepal - Dhungana, Arun Prasad (Journal of Kathmandu Medical College, 2017)
Background: Childhood blindness is a priority area because of the number of years of blindness that ensues. Data on the prevalence and causes of blindness and severe visual impairment in children are needed for planning and evaluating preventive and curative services for children. Objective: The aim of the study is to determine the prevalence of ocular morbidity among school children in eastern Nepal. Method: A cross-sectional study was designed to evaluate ocular status of primary school children in six government schools of the eastern region of Nepal. A complete eye examination was carried out in all children including slit lamp examination, fundus examination, retinoscopy and subjective refraction. Data was analyzed using Microsoft excel. The screening is based on the Indiana school vision screening guideline. Results: A total of 847 children were examined in visits. The mean age of study population was 10.25 years. Among them 450 were males and 397 were females. The results showed that 12.05% of the total students had ocular and visual morbidities. Refractive error was found to be the commonest abnormality (62%) in school children. The commonest type of refractive error found in the study was myopia followed by hyperopia. Alternate divergent squint is the commonest type of strabismus. Other abnormalities found were BSV (binocular single vision) abnormalities, amblyopia and conjunctival disorder. Conclusion: The vision screening program has proved to be very helpful in early detection, diagnosis, referral and management of ocular morbidities in school children. The results of the study strongly suggest that screening of school children for ocular problems should be done at regular intervals and it should be one of the prime components of school health program. Journal of Kathmandu Medical College Vol. 5, No. 3, Issue 17, Jul.-Sep., 2016, page: 95-97